2012
DOI: 10.1007/s10339-012-0480-x
|View full text |Cite
|
Sign up to set email alerts
|

From top to bottom: spatial shifts of attention caused by linguistic stimuli

Abstract: Interacting with the world around us involves dealing with constant information input. Thus, humans must selectively filter and focus attention on relevant aspects for the current situation. The current study investigates orientations of attention after words that do not convey spatial information in their meaning (e.g. cloud, shoe). The current study minimizes both the linguistic demands by simply presenting task-irrelevant words and the visual processing demands by implementing a simple target detection task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
1
20
1
Order By: Relevance
“…Estes et al (2008) first reported that even when word meaning is task-irrelevant, implicit location words (e.g., hat, shoe) still serve as spatial cues for involuntary attentional orientation. In this study, target discrimination performance in an upper or lower screen location was influenced by centrally presented task-irrelevant words (see also : Dudschig, Lachmair, de la Vega, De Filippis, & Kaup, 2012b;Gozli, Chasteen, & Pratt, 2013). Similar effects have been reported in a sentence-based study (Bergen, Lindsay, Matlock, & Narayanan, 2007) and also when verbs (e.g., climb, drop) were utilized as spatial cues (Verges & Duffy, 2009).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Estes et al (2008) first reported that even when word meaning is task-irrelevant, implicit location words (e.g., hat, shoe) still serve as spatial cues for involuntary attentional orientation. In this study, target discrimination performance in an upper or lower screen location was influenced by centrally presented task-irrelevant words (see also : Dudschig, Lachmair, de la Vega, De Filippis, & Kaup, 2012b;Gozli, Chasteen, & Pratt, 2013). Similar effects have been reported in a sentence-based study (Bergen, Lindsay, Matlock, & Narayanan, 2007) and also when verbs (e.g., climb, drop) were utilized as spatial cues (Verges & Duffy, 2009).…”
Section: Introductionsupporting
confidence: 55%
“…Future studies are needed to investigate whether language-space associations are not only limited to words that have an experiential association with space, but also highly specific regarding the response modalities they interact with. For example, it is possible that implicit location words influence both visual processing (e.g., Dudschig et al, 2012b;Estes et al, 2008) as we typically perceive these entities in the upper or lower visual world, and motor responses, as we might occasionally point to these entities (e.g., Lachmair et al, 2011). In contrast, posture-specific emotion words might only affect motor processing, as these emotion-space associations are based in stereotypical behavior (e.g., Darwin, 1872;Frijda, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there is accumulating evidence that there is a spatially oriented mental number line upon which number magnitude is represented (see Göbel, Shaki & Fischer, ; de Hevia, Vallar & Girelli, ; Bueti & Walsh, for reviews). On the other hand, there is a growing body of literature on the association of language with space (e.g., Dudschig, Lachmair, de la Vega, De Filippis & Kaup, , ; ; Kaup, De Filippis, Lachmair, de la Vega & Dudschnig, ; Lachmair, Dudschnig, De Filippis, de la Vega & Kaup, ) suggesting that spatial location information is activated automatically when nouns or adjectives are processed.…”
Section: Discussionmentioning
confidence: 99%
“…A key (and, at first sight, puzzling) feature of the available literature is that words with up/down associations can both interfere with (Bergen, Lindsay, Matlock, & Narayanan, 2007; Dudschig, Lachmair, de la Vega, De Filippis, & Kaup, 2012; Estes et al, 2008; Gozli, Chasteen, & Pratt, 2013; Verges & Duffy, 2009), or facilitate the discrimination of (Chasteen, Burdzy, & Pratt, 2010; Gozli et al, 2013; Zhang et al, 2013), visual targets in congruent locations. Gozli and colleagues (2013) scrutinized this pattern of findings and showed that interference in compatible location occurs only when SOA is short (<400 ms), whereas facilitation is observed at longer SOAs.…”
mentioning
confidence: 99%